OPTIMIZATION OF LAND USE MAPPING USING SENTINEL IMAGERY TO SUPPORT FLOOD DISASTER MITIGATION IN TORUE DISTRICT - Widyastuti Widyastuti; Exsa Putra; Amalia Novarita; Rahmawati Rahmawati (Universitas Sebelas Maret (UNS), 2026)
To mitigate risk, effective land use planning must consider these socioeconomic factors. Numerous natural disasters will be brought on by improper land modification—the interaction between climate change and land-use change, such as deforestation. Different types of land transformation, such as cultivation and reforestation, are understood in varying ways. This study aims to accurately map land use by utilising GIS and Sentinel-2 data to support disaster mitigation efforts in Torue District. This study adopts a spatial approach and a descriptive quantitative method. Descriptive statistics are employed in this study's data analysis to illustrate the spatial characteristics of the study region, based on satellite image interpretation and GIS data processing. The results obtained eight land use classes. High-quality satellite imagery is required for accurate classification. Similarly, between classes and high intra-class variation can complicate the classification process, requiring advanced techniques to improve accuracy. Land use mapping produced eight classes with a total area of 26,467 ha, achieving an Overall Accuracy of 94.43%.